Phase I study of AR-42 and decitabine in acute myeloid leukemia. Issue 6 (11th May 2020) - Liva, Sophia G.; Coss, Christopher C.; Wang, Jiang; Blum, William; Klisovic, Rebecca; Bhatnagar, Bhavana; Walsh, Katherine; Geyer, Susan; Zhao, Qiuhong; Garzon, Ramiro; Marcucci, Guido; Phelps, Mitch A.; et al.
Abstract: This phase I trial sought to determine a biologically safe and effective dose of AR-42, a novel histone deacetylase inhibitor, which would lead to a doubling of miR-29b prior to decitabine administration. Thirteen patients with previously untreated or relapsed/refractory AML were treated at 3 dose levels (DL): AR-42 20 mg qd on d1, 3, 5 in DL1, 40 mg qd on d1, 3, 5 in DL2 and 40 mg qd on d1, 3, 4, 5 in DL3. Patients received decitabine 20 mg/m 2 on d6–15 of each induction cycle and 20 mg/m 2 on d6–10 of each maintenance cycle. One DLT of polymicrobial sepsis and multi-organ failure occurred at DL3. Two patients achieved a CRi and one patient achieved a CR for an ORR of 23.1%. The higher risk features of this patient population and the dosing schedule of AR-42 may have led to the observed clinical response and failure to meet the biologic endpoint.